Celiac disease and Hp infection association in Iran Enfermedades celiacas e infección por Hp en Irán - M. Rostami-Nejad (Revista Espanola de Enfermedades Digestivas, 2009)
Background: we assessed the prevalence, the related symptoms, and the endoscopic and histologic gastric features of celiac disease (CD) in patients with Helicobacter pylori (Hp). Methods: 450 dyspeptic patients were studied. Biopsies of gastric antrum and duodenum, CD serology, and total IgA were obtained. Histological findings were scored with the Marsh-Rostami criteria. Results: 411 (91.3%) patients were Hp positive. Duodenal histology was normal in 385 (85.6%) patients, 124 (27.5%) had duodenitis and 28 (6.2%) showed duodenal abnormalities (Marsh I-IIIc). Twenty three/28 (82.1%) patients with malabsorption pattern were also Hp positive. Serological analysis: 12 of 31 (38.7%) positive patients had abnormal histology (Marsh I,-IIIc). Nine out 450 patients were IgA deficient; none of them was serologically positive for CD. Conclusion: although a high prevalence of Hp infection was found in this study, the relationship between Hp infection and CD was similar to that reported in other geographic areas.